Verbs That Express Passive Hearing in Catalan and French: Semantic Change of the Forms sentir (Catalan) and entendre (French) - Carla Ferrerós-Pagès (Languages, 2022)
This paper aims to study the meanings of passive auditory perception verbs in Catalan (sentir) and French (entendre) with regards to diachronic semantic change and from the point of view of cognitive semantics. These verbs do not originally encode the meaning related to perception, at least not historically. By taking examples drawn from diachronic and synchronic lexicographical sources, I have analyzed the meanings conveyed by these two verbs and their metaphorical and metonymic projections from their origin to their current use. This research provides new data on semantic extensions related to verbs of perception: certain projections that are frequently related to this kind of verb do not always occur in the direction predicted by inter-linguistic studies. Particularly, the study of the evolution in the French form entendre contradicts the expectations that can be drawn from other studies of verbs on this conceptional domain in that it seems to have evolved in the opposite direction, i.e., from intellectual understanding to sensorial perception.